Simulasi Pembentukan Formasi Pola Spasial Untuk Robot Koloni dengan Turing Morphogenetic Function - Tony Tony; Freddy Kurniawan (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
In this research, the authors simulate the spatial pattern formation for a number of robot colonies using the Turing morphogenetic function. Simulation is developed using Microsoft Robotics Developer Studio 2008. Pattern formation is a formation which formed a triangle pattern on the nine pieces of Lego Mindstorms NXT robot. At first robots will form a straight line, then spun in a circle, and eventually formed a triangle pattern formation. Keywords: spatial pattern formation, robot colonies, Turing morphogenetic function